Factors Influencing Touristic Demand Analysis on Glagah Beach as Tourism Object on Kulon Progo Regency - Mohamad Halimi; Rr Fosa Sarassina (Universitas Batanghari Jambi, 2019)
The purpose of this study was to determine the factors that influence tourist demand for Glagah Beach tourism objects in KulonProgo Regency.This research is quantitative research. Data collection used in the study was carried out through questionnaires. The population in this study are all visitors who come to the Glagah Beach tourism object. Taking into the large number of populations that are not known with certainty, then in this study 100 samples were taken. The selected respondents were visitors to the Glagah Beach tourism object who also visited Congot Beach and Kiskendo Goa attractions, both after visiting Glagah Beach and before visiting Glagah Beach. Sampling is done through accidental sampling. Data analysis was performed through multiple regression analysis with the F test, t test, determination test. The results showed that the cost of travel to Glagah Beach tourism objects, the cost of travel to other attractions, and income per month have negative influence to the number of beach tourism objects Glagah, the other hand, Age and Distance variables have positive influence to the number of beach tourism objects Glagah. From this research just Cost of Travel to Glagah Beach tourism objects that influence tourist demand for Glagah Beach Significantly. The contribution of this research is to increase tourist demand for Glagah Beach in KulonProgo Regency.